Fungos filamentosos no trato digestório de larvas de Phylloicus (Trichoptera: Calamoceratidae) em igarapés da Amazônia brasileira - dos Santos, Taides Tavares; de Oliveira, Keyty Almeida; Vital, Marcos José Salgado; Couceiro, Sheyla Regina Marques; de Morais, Paula Benevides (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2018)
Cultivable filamentous fungi were found for the first time in the digestive tract (DT) of larvae of Phylloicus (Trichoptera: Calamoceratidae). Phylloicus larvae (n=137) were collected in low-order streams in the Brazilian Amazon (Roraima, Pará, and Tocantins states) and dissected to obtain DT contents. Filamentous fungi were cultivated from each individual DT. Filamentous fungi presented different morphologies (geometric mean ± standard deviation of morphospecies per DT = 6.2 ± 6.4), as well as significant variation in population size (colony forming units per DT = 8.5 ± 47.0 x 101), among ecological landscapes and among larvae from the same locality. The fact that Phylloicus larvae commonly harbor filamentous fungi in their DT (94.9%) indicates that these microorganisms play important roles in the interaction interface with their hosts, which may be related to the degradation of lignocellulosic substrates. From this perspective, the DT of Phylloicus may represent a source of fungi with biotechnological potential.
Keywords: Aquatic insects; Fungus-insect interactions; Symbiosis